Response Modelling of a Burnt Clay Brick Wall Subjected to Air Blast Loading. - Katusiime, Bridget (Kabale University, 2023)
This research project presents the response modelling of a burnt clay brick wall subjected to air blast loading. The study focuses on the most common masonry unit in Uganda, clay bricks. Failure of the wall has been assessed based on simplified maximum displacement and stress failure criteria developed in the report. Although modelling debris is beyond the scope of this study, standoff distance between the explosive and the wall has been used as a safety parameter. Iterations have been carried out for different wall model types using Abaqus software. The wall was first modelled on its own with a series of variations and then two mitigation measures were taken into account to strengthen the wall, these were reinforcing wall in a concrete frame and using fibre. Changes and trends observed have been discussed and some conclusions and recommendations made.